Diabetes aggravates periodontitis by limiting repair through enhanced inflammation - Pacios, Sandra (Federation of American Societies for Experimental Biology, 2012)
Periodontitis is the most common lytic bone disease and one of the first clinical manifestations of diabetes. Diabetes increases the risk of periodontitis. The aim of the present study was to examine mechanisms by which diabetes aggravates periodontitis. Ligature-induced periodontitis was examined in Goto-Kakizaki rats with type 2 diabetes. A tumor necrosis factor (TNF)-specific-inhibitor, pegsunercept, was applied to diabetic rats after the onset of periodontal disease. Interferon-γ (IFN-γ), TNF-α, interleukin-1 β (IL-1β), fibroblast growth factor-2 (FGF-2), transforming growth factor beta-1 (TGFβ-1), bone morphogenetic protein-2 (BMP-2), and BMP-6 were measured by real-time RT-PCR, and histological sections were examined for leukocyte infiltration and several parameters related to bone resorption and formation. Inflammation was prolonged in diabetic rats and was reversed by the TNF inhibitor, which reduced cytokine mRNA levels, leukocyte infiltration, and osteoclasts. In contrast, new bone and osteoid formation and osteoblast numbers were increased significantly vs. untreated diabetic animals. TNF inhibition in diabetic animals also reduced apoptosis, increased proliferation of bone-lining cells, and increased mRNA levels of FGF-2, TGFβ-1, BMP-2, and BMP-6. Thus, diabetes prolongs inflammation and osteoclastogenesis in periodontitis and through TNF limits the normal reparative process by negatively modulating factors that regulate bone.—Pacios, S., Kang, J., Galicia, J., Gluck, K., Patel, H., Ovaydi-Mandel, A., Petrov, S., Alawi, F., Graves, D. T. Diabetes aggravates periodontitis by limiting repair through enhanced inflammation.